Effect of melatonin on antioxidant capacity, ınflammation and apoptotic cell death in lung tissue of diabetic rats - Onk,Didem (2018)
Abstract Purpose: To investigate the effects of melatonin on antioxidant capacity, inflammation and apoptotic cell death (through expression of cleaved-caspase 3) in lung tissue samples of diabetic rats. Methods: Thirty male Sprague-Dawley rats were randomly divided into three groups. Group 1 (control group) was made up of healthy rats. Group 2 (diabetes group) received streptozotocin at a dose of 50 mg/kg/day for 5 days.Group 3 (diabetes plus melatonin group) received streptozotocin at a dose of 50 mg/kg/day for 5 days and then they received melatonin at a dose of 20 mg/kg/day between 28thand 35thdays of the study. Results: Tissue MDA and MPO levels were found to be significantly higher in diabetes group compared to control group (p<0.05) whilst administration of melatonin was found to significantly lower this increase down to normal levels (p<0.05). Bronchus associated lymphoid tissue (BALT) was more severe in diabetics whereas administration of melatonin alleviated this hyperplasia. Cleaved caspase 3 activity was severe in hyperplastic BALT in diabetic rats however in lowered down to moderate level when melatonin was administered. Conclusion: The melatonin caused an increase in antioxidant capacity and decreased the expression of cleaved-caspase 3.